Wheel gymnastics - somersault dismounts and no landing mat - Knoll, Kl.; Hildebrand, F.; Drenk, V.; Sebesta, I. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The aim of this study was to investigate which biomechanical principles act during salto dismounts from the gymwheel and in which way the load during landing can be reduced. For this purpose a forward and a backward somersault dismount from straight-line voluntary routines were studied. The movement of the gymnast and the wheel were analyzed with a 3D photogrammetric procedure. Flight height and salto angular momentum can be increased if the take-off is improved. For example, the wheel velocity has to decelerated during the take-off to zero in order to transmit a bigger amount of energy back to the gymnast. The maximum loads while landing from approx. 2.50 m height on the hard ground can be reduced by suitable movements of the body segments. But we recommend to the I.R.V., though, to introduce landing mats in the straight-line discipline too.